2019
DOI: 10.1002/jcb.28734
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor‐1 promotes liver fibrosis in nonalcoholic fatty liver disease by activating PTEN/p65 signaling pathway

Abstract: Obesity is a major contributor to the development of steatohepatitis and fibrosis from nonalcoholic fatty liver disease (NAFLD). Hypoxia aggravates progression of NAFLD. In mice on high‐fat diet (HFD), hepatic steatosis leads to liver tissue hypoxia, evidenced by accumulation of hypoxia inducible factor‐1‐alpha (HIF‐1α), which is a central regulator of the global response to hypoxia. Hepatocyte cell signaling is an important factor in hepatic fibrogenesis. We here hypothesize that HIF‐1α knockout in hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 42 publications
(79 reference statements)
1
45
0
1
Order By: Relevance
“…Cxcl1 , Cxcl11 , Hif1a , Col4a1 , and Fn1 were unexpectedly elevated in the liver of MPF versus EF mice, suggesting that SFB within the complex commensal gut microbiota leads to proinflammatory innate immune response effects in the liver. Astonishingly, these findings are in line with seminal reports demonstrating that CXCL1, CXCL11, HIF1A, COL4A1, and FN1 are implicated in liver fibrosis …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Cxcl1 , Cxcl11 , Hif1a , Col4a1 , and Fn1 were unexpectedly elevated in the liver of MPF versus EF mice, suggesting that SFB within the complex commensal gut microbiota leads to proinflammatory innate immune response effects in the liver. Astonishingly, these findings are in line with seminal reports demonstrating that CXCL1, CXCL11, HIF1A, COL4A1, and FN1 are implicated in liver fibrosis …”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, CXCL11 has also been shown to endorse T H 1 cell proinflammatory cytokine production and facilitate T H 17 cell development in an experimental colitis model . Hypoxia inducible factor 1 ( Hif1a ), collagen type IV ( Col4a1 ), and fibronectin ( Fn1 ) are profibrotic factors that promote liver fibrosis . Considering that SFB colonization within a complex gut microbiota increased serum IL17A levels (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hypoxia-inducible factor 1 alpha (HIF-1α) is known to be a key regulator of a tissue's response to hypoxia [26] and plays a role in obesity-induced metabolic syndrome. It has been shown that HFD leads to gradual increase in HIF-1α and associated pathological changes in the liver [27,28]. However, the role of HIF-1α in the retina of WD-fed mice is not known.…”
Section: Introductionmentioning
confidence: 99%